Thermodynamic properties of the generalized Murnaghan equation of state of solids - Fernández Guillermet, Armando (Comisión Nacional de Energía Atómica; Argentina)
Fil: Fernández Guillermet, Armando Comisión Nacional de Energía Atómica; Argentina